The Importance of Stylistic Research in Uzbek Linguistics - Ne’matova Malikaxon Zafarjon qizi (Genius Journals, 2025)
This article presents views on scientific research conducted in the field of stylistics, stylistic devices, and their types.
Keywords: style; manner; poetics; metaphor